PERAMALAN MENGGUNAKAN METODE DOUBLE EXPONENTIAL SMOOTHING DAN VERIFIKASI HASIL PERAMALAN MENGGUNAKAN GRAFIK PENGENDALI TRACKING SIGNAL (STUDI KASUS: DATA IHK PROVINSI KALIMANTAN TIMUR) - Habsari, Humairo Dyah Puji; Purnamasari, Ika; Yuniarti, Desi (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
This study uses IHK data from East Kalimantan Province in January 2016 to February 2019, which has a patterned trend. Data that shows a trend, can use double exponential smoothing forecasting one parameter from Brown and two parameters from Holt. The purpose of this study is to determine the best double exponential smoothing forecasting method based on the smallest MAPE value and verify the best forecasting method based on the tracking signal control chart. Based on the MAPE value of 0.361% and the control chart tracking signal value, the results of the study show that the best forecasting method is the two-parameter double exponential smoothing method of Holt with parameters and .